2020
DOI: 10.3390/foods9050604
|View full text |Cite
|
Sign up to set email alerts
|

Valorisation of Grape Stems as a Source of Phenolic Antioxidants by Using a Sustainable Extraction Methodology

Abstract: Pressurized liquid extraction with ethanol:water mixtures was proposed for obtaining phenolic antioxidants from grape stems. The optimal extraction conditions were elucidated by using a central composite rotatable design (solvent (X1, 0–100% ethanol:water v/v), temperature (X2, 40–120 °C) and time (X3, 1–11 min)). Response surface methodology determined 30% ethanol:water, 120 °C and 10 min as the optimal extraction conditions regarding total phenolic content (TPC) (185.3 ± 2.9 mg gallic acid/g of extract) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 38 publications
5
25
0
Order By: Relevance
“…Then, the combination of a medium polar solvent (ethanol) with a high polar solvent (water) was the most suitable alternative to obtain high yields in the extraction of licorice root. These results are in accordance to other reported extraction studies, such as the work of Nieto et al [39] concerning the extraction of grape stems, Arranz et al [40] in the extraction of marjoram with different ethanol:water mixtures, or Kaderides et al [41] in the UAE extraction of pomegranate peels, reporting an increase in the extraction yield with an increase in solvent polarity. Moreover, it was found that the combination of solvents is more efficient for extraction of phenolic compounds than a single solvent [42].…”
Section: Extraction Yield Of Licorice Extracts and Quantification Of Bioactive Compoundssupporting
confidence: 92%
“…Then, the combination of a medium polar solvent (ethanol) with a high polar solvent (water) was the most suitable alternative to obtain high yields in the extraction of licorice root. These results are in accordance to other reported extraction studies, such as the work of Nieto et al [39] concerning the extraction of grape stems, Arranz et al [40] in the extraction of marjoram with different ethanol:water mixtures, or Kaderides et al [41] in the UAE extraction of pomegranate peels, reporting an increase in the extraction yield with an increase in solvent polarity. Moreover, it was found that the combination of solvents is more efficient for extraction of phenolic compounds than a single solvent [42].…”
Section: Extraction Yield Of Licorice Extracts and Quantification Of Bioactive Compoundssupporting
confidence: 92%
“…Obviously, D. katangensis (ME IC50 = 0.58 μg/mL) exhibits an antioxidant activity greater than that of the above-mentioned plant species. According to the classification proposed previously [20], this antioxidant activity of D. katangensis is very good and would very probably be linked to the presence of the polyphenolic compounds identified (Table 1) and quantified (Table 2) during this study, especially since phenolic compounds are known as antioxidants [46][47][48].…”
Section: Discussionmentioning
confidence: 52%
“…The pretreatment of the samples, the extraction technique, as well as the solvent used may have a significant influence on the recovery of PhCs from natural matrices [ 18 ]. Even though a high number of studies show that acetone and methanol lead to the highest yield of individual extraction of polyphenols, hydroethanolic mixtures had shown a better recovery rate of total polyphenols [ 19 ]. Considering the solvent choice, ethanol is considered the best option for further incorporation of the extracts in oral care products due to its efficiency, low toxicity, and GRAS status.…”
Section: Active Compounds In V Vinifera By-promentioning
confidence: 99%
“…Considering the solvent choice, ethanol is considered the best option for further incorporation of the extracts in oral care products due to its efficiency, low toxicity, and GRAS status. Moreover, ethanol has the advantage of being reusable and environmentally friendly solvent [ 19 , 20 ]. Table 1 presents the main PhCs identified in V. vinifera by-products along with the extraction parameters using suitable solvents for cosmetic and pharmaceutical applications.…”
Section: Active Compounds In V Vinifera By-promentioning
confidence: 99%